HU protein is involved in intracellular growth and full virulence of Francisella tularensis - Stojkova, Pavla; Spidlova, Petra; Lenco, Juraj; Rehulkova, Helena; Kratka, Lucie; Stulik, Jiri (Virulence, 2018)
The nucleoid-associated HU proteins are small abundant DNA-binding proteins in bacterial cell which play an important role in the initiation of DNA replication, cell division, SOS response, control of gene expression and recombination. HU proteins bind to double stranded DNA non-specifically, but they exhibit high affinity to abnormal DNA structures as four-way junctions, gaps or nicks, which are generated during DNA damage. In many pathogens HU proteins regulate expression of genes involved in metabolism and virulence. Here, we show that the Francisella tularensis subsp. holarctica gene locus FTS_0886 codes for functional HU protein which is essential for full Francisella virulence and its resistance to oxidative stress. Further, our results demonstrate that the recombinant FtHU protein binds to double stranded DNA and protects it against free hydroxyl radicals generated via Fenton's reaction. Eventually, using an iTRAQ approach we identified proteins levels of which are affected by the deletion of hupB, among them for example Francisella pathogenicity island (FPI) proteins. The pleiotropic role of HU protein classifies it as a potential target for the development of therapeutics against tularemia.
Keywords: DNA-Binding Proteins; Virulence Factors; Gene Expression Profiling; Protein Binding; Gene Deletion; DNA; Stress, Physiological; virulence; HU protein; Francisella tularensis; Oxidative Stress; fyziologický stres; DNA binding protein; Bacterial Proteins; FPI; delece genu; Virulence; vazba proteinů; nucleoid-associated protein; DNA vazebné proteiny; stanovení celkové genové exprese; oxidační stres; faktory virulence; Francisella; bakteriální proteiny